Dari Karisma Menuju Sistem: Transformasi Kepemimpinan Kiai dalam Manajemen Pengelolaan Pesantren (Studi Literatur) - Rasti Astuti Laisaan; Muhammad Husni (Jurnal Manajemen dan Ilmu Administrasi, 2026)
The transformation of pesantren leadership has become a significant issue in the management of contemporary Islamic education due to increasing demands for professionalism, organizational complexity, and institutional governance modernization. Traditionally, pesantren leadership has relied heavily on the charismatic authority of the kiai, who serves as the central figure in decision-making processes, organizational culture formation, and socio-religious legitimacy. Although this leadership model has been effective in preserving the identity and values of pesantren, the dominance of a central figure also creates several institutional challenges, including organizational dependency, weak leadership regeneration, limited authority distribution, and inadequate governance standardization. This study aims to analyze the construction of charismatic kiai leadership, examine the transformation of pesantren leadership toward system-based governance, and formulate an ideal model of contemporary pesantren leadership. This study employed a qualitative approach using the Narrative Literature Review method. Data were collected from national and international journal articles, books, theses, dissertations, and scientific proceedings related to pesantren leadership, organizational transformation, and Islamic education management. Data analysis was conducted through content analysis involving data reduction, thematic categorization, literature synthesis, and conceptual interpretation. The findings reveal that pesantren leadership transformation has shifted from a person-centered leadership model toward a more professional, collective, and adaptive institutional leadership model. This transformation is characterized by strengthening institutional systems, authority distribution, implementation of modern governance, administrative digitalization, and the development of collaborative leadership without eliminating the spiritual legitimacy of the kiai. This study proposes the Spiritual-Systemic Leadership Model, which integrates the spiritual charisma of the kiai with modern organizational systems based on professionalism, collective leadership, Islamic value-based governance, and sustainable institutional evaluation. The model represents a synthesis between preserving pesantren traditions and meeting the demands of organizational transformation in the modern era.